2013
DOI: 10.1089/aid.2012.0143
|View full text |Cite
|
Sign up to set email alerts
|

Effect of HIV Type 1 Subtype on Virological and Immunological Response to Combination Antiretroviral Therapy: Evidence for a More Rapid Viral Suppression for Subtype A Than Subtype B-Infected Greek Individuals

Abstract: Whether response to combination antiretroviral therapy (cART) differs between those infected with HIV-1 subtype A or B remains unclear. We compared virological and immunological response to cART in individuals infected with subtype A or B in an ethnically homogeneous population. Data derived from the Athens Multicenter AIDS Cohort Study (AMACS) and analysis were restricted to those of Greek origin. Time to virological response (confirmed HIV-RNA <500 copies/ml) and time to failure (>500 copies/ml at any time o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
0
9
0
1
Order By: Relevance
“…In addition, the increasing genetic heterogeneity of HIV‐1 worldwide might have consequences for virological and immunological responses to antiretroviral therapy (ART), which may vary by HIV‐1 subtype or genotype, and are of high clinical relevance. Improved virological but similar immunological responses have been observed among patients infected with non‐B clades or different recombinant forms versus subtype B . In particular, those infected with HIV‐1 subtype A or CRF02_AG had better outcomes than those infected with subtype B .…”
Section: Introductionmentioning
confidence: 60%
“…In addition, the increasing genetic heterogeneity of HIV‐1 worldwide might have consequences for virological and immunological responses to antiretroviral therapy (ART), which may vary by HIV‐1 subtype or genotype, and are of high clinical relevance. Improved virological but similar immunological responses have been observed among patients infected with non‐B clades or different recombinant forms versus subtype B . In particular, those infected with HIV‐1 subtype A or CRF02_AG had better outcomes than those infected with subtype B .…”
Section: Introductionmentioning
confidence: 60%
“…20 Previous studies have reported more rapid viral suppression in individuals with certain HIV subtypes. 21,22 …”
Section: Discussionmentioning
confidence: 99%
“…Over the last 15 years, the molecular epidemiology of different HIV-1 subtypes and CRFs, referred to hereafter as HIV-1 clades, in Europe has significantly changed becoming more heterogeneous Hemelaar et al, 2011). The increasing complexity raises plausible questions about potential issues in diagnosis, clinical management and even in pathogenesis (Camacho, 2006;Chaix et al, 2013;Easterbrook et al, 2010;Geretti et al, 2009;Hemelaar, 2013;Paraskevis et al, 2013b;Santoro and Perno, 2013;Scherrer et al, 2011;Siemieniuk et al, 2013;Touloumi et al, 2013). Investigation of the European HIV-1 epidemic by means of molecular epidemiology provides valuable information to investigate and monitor the epidemic's dynamics over time (Frost and Pillay, 2015;Kuhnert et al, 2014;Pybus and Rambaut, 2009;Stadler and Bonhoeffer, 2013;Stadler et al, 2012).…”
Section: Introductionmentioning
confidence: 99%